Effects of Health Status and Health Behaviors on Depression Among Married Female Immigrants in South Korea - Jung A Kim, PhD; Sook Ja Yang, PhD; Yeon Kyung Chee, PhD; Kyoung Ja Kwon, PhD; Jisook An, PhD (Elsevier, 2015)
Purpose: This study examined the effects of health status and health behaviors on depression in married female immigrants in South Korea. Methods: Sampling 316 immigrant women from the Philippines, Vietnam, China, and other Asian countries, a cross-sectional research design was used with self-report questionnaires that assessed sociodemographic characteristics, health status, health behaviors, and depression. Results: There were significant differences in stillbirth experience, induced abortion, morbidity, perceived health status, meal skipping, and physical activity between depressed and nondepressed immigrant women. After adjusting for sociodemographic variables, stillbirth experience, poorer perceived health status, more meal skipping, and less physical activity were associated with greater depressive symptoms. Conclusions: Both health status and health behaviors had significant impacts on depression, suggesting that development of nursing interventions and educational programs should be targeted towards improving maternal health, healthy lifestyle, and subjective health perception to promote married female immigrants' psychological well-being.